Am I safe?: the ventrolateral prefrontal cortex ‘detects’ when an unpleasant event does not occur - Bender, Stephan; Hellwig, Stefanie; Resch, Franz; Weisbrod, Matthias (NeuroImage, 2007)
The ventrolateral prefrontal cortex (VLPFC) is implicated in contingency detection and the evaluation of emotionally significant stimuli. However, the mechanisms whereby an individual can effectively avoid painful or unpleasant events are not well understood. We therefore examined whether the absence of an unpleasant somatosensory stimulus could evoke a response in the human VLPFC as a correlate of contingency detection (the feeling that “I am safe”) without any immediately preceding stimulus. In a differential trace-conditioning paradigm, the unpleasant stimulus followed the partially reinforced stimulus in 50% of trials after 3 s; it never occurred after the nonreinforced stimulus. High-resolution DC electroencephalography, current source density mapping, and spatio-temporal source analysis were performed. After the nonreinforced stimulus, a highly significant negativity over the VLPFC began about a second after the time for the unpleasant stimulus to occur had passed. We concluded that the VLPFC can be activated merely by a sequence of stimuli (with long interstimulus intervals) without any directly preceding stimulus, provided that this sequence creates the expectation that at a certain time an unpleasant stimulus might occur. This mechanism might allow for the detection of conditions under which harmful events could be avoided. Moreover, in reinforced trials, we found a highly significantly lateralized negativity (N700) that outlasted the strong, unpleasant somatosensory stimulus for about a second. Topography and source analysis pointed to prolonged activation of the somatosensory system. This processing stage preceded activation of the VLPFC. We concluded that N700 might provide important insights into the time course of somatosensory memory traces.